ANALISIS MODEL ALTMAN (Z-SCORE) DALAM MENGUKUR KINERJA KEUANGAN UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA (BEI) PERIODE 2010-2014 - Kakauhe, Anastasya Claudio Inri; Pontoh, Winston (Universitas Sam Ratulangi, 2017)
The purpose of this research to prediction bankruptcy on company for 5 (five) financial period Â Â 2010 to 2014 using the Altman Z-Score Model. The sampling technique used is using purposive sampling technique with the sampling criteria is a company manufacturing consumer goods industry sector listed in Indonesia Stock Exchange (BEI) and publish regular financial statements for 2010-2014. These results indicate that the model atlman Z-Score can be implemented in companies manufacturing consumer goods industry sector and can be grouped in three categories: companies which indicated that are in the healthy category, the company indicated in the category gray areas or potential bankruptcy and enterprise indicated in the category bankrupt. Suggestions for the company, as indicated in the category bankrupt and gray areas or potential bankruptcy, it's worth making improvements to the sales and performance of the company in order to reduce the decline in the sales and the decline of the assets that would result in losses. Meanwhile, the company indicated in the category of healthy, should continue to maintain and improve the performance of the company in order to avoid losses.Keywords : Bankcruptcy, Altman Z-Score